1996
DOI: 10.1183/09031936.96.09010042
|View full text |Cite
|
Sign up to set email alerts
|

Minimal dose of aerosolized interferon-alpha in human subjects: biological consequences and side-effects

Abstract: Interferon-α (IFN-α) is a leucocyte-derived cytokine with pleiotropic effects on the cells of the immune system, including the ability to promote viral and microbial killing. This study was designed to evaluate the biologically active dosage of aerosolized lymphoblastoid IFN-α, in normal subjects and patients with chronic bronchitis, using serum 2'-5' oligoadenylate synthetase (OAS) as a marker of IFN-α actitivity.Three groups of subjects were included: two healthy groups and one of patients with chronic bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As previously shown, this cytokine can be safely delivered to the epithelial surface of the lower respiratory tract without systemic side effects (10). To establish possible mechanisms involved in infection control by IFN-␣, we evaluated several biologic, clinical, and biochemical variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously shown, this cytokine can be safely delivered to the epithelial surface of the lower respiratory tract without systemic side effects (10). To establish possible mechanisms involved in infection control by IFN-␣, we evaluated several biologic, clinical, and biochemical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work found that aerosolized IFN-␣ administration to the lung was well tolerated at biologically active doses. 2 Ј -5 Ј Olygoadenilate synthetase (OAS) levels, used as a marker of IFN-␣ activity, increased after local treatment in serum and bronchoalveolar lavage fluid (BALF), suggesting that the inhaled cytokine was active at lung level (9,10).…”
mentioning
confidence: 99%
“…Thus, type I IFN may be critical for the innate immune response to Mtb infection. In clinical studies a beneficial effect of treatment of tuberculosis patients with inhaled IFN-␣ has been observed (64,65), and people with STAT1 mutations are susceptible to mycobacterial infections, demonstrating a protective role of IFNs (66). In contrast, treatment of human monocytes with IFN-␣␤ resulted in increased growth of M. bovis Calmette-Guérin bacillus, and intranasal instillation of IFN-␣␤ in Mtb-infected mice increased mycobacterial growth and impaired mouse survival (59,67).…”
Section: Discussionmentioning
confidence: 99%
“…The potent antifibrotic effects of IFNγ have also attracted attention as a therapy for idiopathic pulmonary fibrosis . Of relevance to the inhaled delivery of IFNs, both IFNα and IFNγ have been shown to be physically stable upon aerosolization and exhibit good tolerability when delivered directly to the lungs …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Of relevance to the inhaled delivery of IFNs, both IFN" and IFN( have been shown to be physically stable upon aerosolization and exhibit good tolerability when delivered directly to the lungs. 13,14 The IFNs are separated into several classes that differ in their biological activity. Type I IFNs (which include subtypes " and $) exist as single polypeptides that primarily exert antiviral activity, but can also inhibit cellular proliferation.…”
Section: Introductionmentioning
confidence: 99%